An Evolutionary Model of Industry Transformation and the Political Sustainability of Emission Control Policies - Isley, Steven C. (RAND Corporation, 2013)
Limiting climate change will require transformation of energy and other systems. This report presents an agent-based, game theoretic model designed to compare the long-term sustainability of alternative carbon emission reduction policies. The model tracks the co-evolution of an industry sector, its technology base, and political coalitions that influence government policy. It uses robust decision making methods to compare alternative policies.